Genome wide identification and characterization of EPFL genes and its potential association with male sterility in Brassica rapa - Kang Wang; Yongkang Wang; Xiaoyan Tang; Na Liao; Danni Yang; Wenjie Wang; Lingyun Yuan; Jinfeng Hou; Jianqiang Wu; Chenggang Wang; Guohu Chen (Scientific Reports)
Abstract The epidermal patterning factor-like (EPFL) gene family, encoding cysteine-rich polypeptides (CRPs), regulates diverse developmental processes in plants, including the control of stomatal density and the guidance of pollen tube elongation. To investigate its potential association with male sterility in Brassica rapa, we performed a comprehensive genome-wide identification using bioinformatics approaches. Our analysis revealed 14 BrEPFL members distributed across 8 of the 10 chromosomes. Phylogenetic analysis of EPFL proteins from 15 Brassicaceae species classified 204 orthologous genes into six distinct subfamilies, revealing their evolutionary conservation across crucifers. Syntenic collinearity and nonsynonymous/synonymous (Ka/Ks) analyses identified 63 orthologous gene pairs between B. rapa and three other species, all of which have undergone strong purifying selection during evolution. Tissue-specific expression profiling through RNA-seq and RT-qPCR demonstrated that most BrEPFL genes exhibit predominant expression in reproductive tissues. Co-expression network analysis implicated three BrEPFL coexpressed genes (BraA07g025640.3 C, BraA09g052700.3 C, and BraA10g002620.3 C) in pollen development pathways. These findings may provide valuable information for the further understanding of BrEPFL functions in male sterility in B. rapa.